Case report: 7p22.3 deletion and 8q24.3 duplication in a patient with epilepsy and psychomotor delay—Does both possibly act to modulate a candidate gene region for the patient’s phenotype? - Touhami, Rahma; Foddha, Hajer; Alix, Eudeline; Jalloul, Afef; Mougou-Zerelli, Soumaya; Saad, Ali; Sanlaville, Damien; Haj Khelil, Amel (Frontiers in Genetics, 2023)
Abstract Background: Psychomotor delay, epilepsy and dysmorphic features are clinical signs which are described in multiple syndromes due to chromosomal imbalances or mutations involving key genes implicated in the stages of Early Embryonic Development. In this context, we report a ten years old Tunisian patient with these three signs. Our objective is to determine the cause of developmental, behavioral and facial abnormalities in this patient. Methods: We used banding cytogenetics (karyotype) and Array Comparative Genomic Hybridization (Array CGH) to this purpose. Results: The karyotype was in favor of a derivative of chromosome 7 in the patient and Array CGH analysis revealed a loss of genetic material in 7p22.3-p22.1 (4,56 Mb) with a gain at 8q24.23-q24 resulting from maternal 7/8 reciprocal translocation. An in-silico analysis of the unbalanced region was carried out and showed that the 7p22.3-p22.1 deletion contains 8 genes. Among them, BRAT1 gene, previously described in several neurodevelopmental diseases, may be a candidate gene which absence could be correlated to the patient’s phenotype. However, the 8q24.23-q24 duplication could be involved in the phenotype of this patient. Conclusion: In this study, we report for the first time a 7p deletion / 8q duplication in a patient with psychomoteur delay, epilepsy and facial dysmorphism. Our study showed that Array CGH still useful for delivering a conclusive genetic diagnosis for patients having neurodevelopmental abnormalities in the era of next-generation sequencing, Key words: Psychomotor delay, Epilepsy, facial dysmorphism, Array CGH, deletion/duplication, BRAT1 gene.